Cross-cultural competence for a twenty-first-century military : culture, the flipside of COIN - Sands, Robert Greene, 1957- (Lexington Books, 2014)
Cross-Cultural Competence for a Twenty-First-Century Military: Culture, the Flipside of COIN suggests that the application of cross-cultural competence to the unique environment of expeditionary deployment through military objectives is one of the most important force enablers in today's U.S. international security mission. This volume will make immediate and long-lasting contributions to research, learning, and policy in the Department of Defense. Its contributors are many of the leading experts and military operators in a multidisciplinary effort to prepare U.S. military and civilian personnel for expeditionary missions.